"We can keep the fire burning": building action competence through environmental justice education in Uganda and Germany. Issue 2 (1st February 2018) - Dittmer, Livia; Mugagga, Frank; Metternich, Alexander; Schweizer-Ries, Petra; Asiimwe, George; Riemer, Manuel
ABSTRACT: The global dimensions of climate change necessitate a response that takes national differences – social, economic, geographic, and cultural – into account. Action-oriented education has a key role to play in advancing citizen engagement in a culture of sustainability. This paper describes research conducted with one such education programme, Youth Leading Environmental Change (YLEC), which operates in six countries and engages university-aged youth in discussion and practice related to global sustainability, systems thinking, and environmental justice. YLEC aims to advance four key competencies; this paper focuses on the goal of action competence, which involves acquiring knowledge, reflecting on experience in the context of one's values, envisioning alternative futures, and acting individually and collectively to advance those alternatives. The present article examines the impacts of YLEC on environmental action competence in two of the countries involved in this research: Uganda and Germany. In-depth interviews were conducted with participants in both countries to examine the development of action competence during and after the programme. Findings suggest that outcomes differed in each country, reflective of participants' different lived experiences. YLEC effectively built on the conditions faced in each country to accompany youth to a higher level of awareness and action. These findings have implications for environmental education programmes striving to work with multiple nations and diverse participants.